Islamic Boarding School Curriculum Management at Daarut Tauhiid Boarding School - Lutpi Mubarok; Badrudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Curriculum management is one aspect that influences the success of learning in educational institutions. This research aims to identify the planning, implementation, organization and management control of Islamic boarding school curriculum development at the Daarut Tauhiid Islamic Boarding School. This research uses a qualitative approach. Research data was collected through in-depth interviews, participant observation, and document analysis. To find out that the data collected in this research was correct, a data validity test was carried out using triangulation techniques. The research conducted shows that management of the Islamic boarding school curriculum at the Daarut Tauhiid Islamic Boarding School is carried out systematically through four main stages: planning, organizing, implementing and controlling. In planning, a workshop was carried out by the quality standards development team (TPSM) with the assistance of expert consultants, the results of which were agreed upon by the school principal. Organizing was carried out by forming a TPSM to supervise curriculum implementation. Implementation is carried out through pre-processal, processional and evaluation stages. Control is carried out by direct supervision, unannounced inspections, periodic briefings, as well as evaluation of learning outcomes by musyrif through exams.